RRM2 and CDC6 are novel effectors of XBP1-mediated endocrine resistance and predictive markers of tamoxifen sensitivity - David Barua; Afrin Sultana; Md Nahidul Islam; Fergus Cox; Ananya Gupta; Sanjeev Gupta (BMC Cancer, 2023)
Abstract Background Endocrine-resistant breast cancers have elevated expression of XBP1, where it drives endocrine resistance by controlling the expression of its target genes. Despite the in-depth understanding of the biological functions of XBP1 in ER-positive breast cancer, effectors of endocrine resistance downstream of XBP1 are poorly understood. The aim of this study was to identify the XBP1-regulated genes contributing to endocrine resistance in breast cancer. Methods XBP1 deficient sub-clones in MCF7 cells were generated using the CRISPR-Cas9 gene knockout strategy and were validated using western blot and RT-PCR. Cell viability and cell proliferation were evaluated using the MTS assay and colony formation assay, respectively. Cell death and cell cycle analysis were determined using flow cytometry. Transcriptomic data was analysed to identify XBP1-regulated targets and differential expression of target genes was evaluated using western blot and qRT-PCR. Lentivirus and retrovirus transfection were used to generate RRM2 and CDC6 overexpressing clones, respectively. The prognostic value of the XBP1-gene signature was analysed using Kaplan–Meier survival analysis. Results Deletion of XBP1 compromised the upregulation of UPR-target genes during conditions of endoplasmic reticulum (EnR) stress and sensitized cells to EnR stress-induced cell death. Loss of XBP1 in MCF7 cells decreased cell growth, attenuated the induction of estrogen-responsive genes and sensitized them to anti-estrogen agents. The expression of cell cycle associated genes RRM2, CDC6, and TOP2A was significantly reduced upon XBP1 deletion/inhibition in several ER-positive breast cancer cells. Expression of RRM2, CDC6, and TOP2A was increased upon estrogen stimulation and in cells harbouring point-mutants (Y537S, D538G) of ESR1 in steroid free conditions. Ectopic expression of RRM2 and CDC6 increased cell growth and reversed the hypersensitivity of XBP1 KO cells towards tamoxifen conferring endocrine resistance. Importantly, increased expression of XBP1-gene signature was associated with poor outcome and reduced efficacy of tamoxifen treatment in ER-positive breast cancer. Conclusions Our results suggest that RRM2 and CDC6 downstream of XBP1 contribute to endocrine resistance in ER-positive breast cancer. XBP1-gene signature is associated with poor outcome and response to tamoxifen in ER-positive breast cancer.